Comorbidity of dyslipidemia and periodontal diseases - Dmitry I. Trukhan; Anatoly F. Sulimov; Larisa Yu. Trukhan (LLC "MEDIAFORMAT", 2024)
Dyslipidemia - increased blood levels of cholesterol, triglycerides and atherogenic lipoproteins and/or decreased levels of anti-atherogenic high-density lipoproteins. Dyslipidemia is considered one of the main biological risk factors for chronic non-communicable diseases, along with overweight and obesity, arterial hypertension and hyperglycemia. The initial stage of correction of dyslipidemia begins with dietary recommendations, in which omega-3 polyunsaturated fatty acids occupy an important place. The effects of the main substances included in the combined nutraceutical Cholesterol Control are considered: omega-3 polyunsaturated fatty acids, including eicosapentaenoic and docosahexaenoic acids, red yeast rice, coenzyme Q10, which allows us to consider it the nutraceutical of choice for low and moderate risk individuals with moderately elevated cholesterol and triglycerides, no indications for taking statins or the presence of contraindications to taking them. Periodontitis is the sixth most common disease in the world (second among dental pathologies after caries) and the leading cause of tooth loss in adults. At the beginning of the 21st century, the concept of "periodontal medicine" was formed, within the framework of which the bidirectional connection of periodontal pathology with systemic diseases of the body is considered. We searched the PubMed and Scopus information databases for articles published before 02/15/2024 that examined the relationship between dyslipidemia and periodontal pathology. The results obtained indicate the presence of a bidirectional relationship between dyslipidemia and periodontal pathology. The analysis showed the positive effect of omega-3 polyunsaturated fatty acids and coenzyme Q10 on the inflammatory process in periodontal tissue and allows us to consider the nutraceutical Cholesterol Control as an adjuvant therapy in comorbid patients with dyslipidemia and periodontal pathology, as well as for the prevention of lipid disorders in patients with periodontal diseases.